Pavimenta Potentina: il contributo delle attestazioni pavimentali per la ricostruzione di un centro urbano poco noto della Lucania romana - Donnici, Fabio (O T I V M, 2024)
Ancient floors, if properly analysed in their different features and led back to their own archaeological contexts, could contribute in a significant way to the overall knowledge of the specific areas in which they were made and used. This informative value turns out to be particularly in the event of little-known ancient sites, such as Potentia, a Roman city of Lucania (Regio III) with extremely poor archaeological (and historical) evidence. In this contribution a collection and a critical analysis of the roman pavements found in the city and in its suburbium is proposed. The aim is to reconstruct the wider settlement and cultural framework of the city over time, as well as to provide new insights for future researches.